Inter-rater and intra-rater agreement of [99mTc]-labelled NM-01, a single-domain programmed death-ligand 1 (PD-L1) antibody, using quantitative SPECT/CT in non-small cell lung cancer - Daniel Johnathan Hughes; Gitasha Chand; Jessica Johnson; Damion Bailey; Kathryn Adamson; Vicky Goh; Gary J. R. Cook (EJNMMI Research, 2023)
Abstract Background Immune checkpoint inhibitors, including those against programmed cell death protein-1 (PD-1) or its ligand (PD-L1), are routinely used to treat non-small cell lung cancer (NSCLC). PD-L1 is a validated prognostic and predictive immunohistochemical biomarker of anti-PD-1/PD-L1 therapy but displays temporospatial heterogeneity of expression. Non-invasive radiopharmaceutical techniques, including technetium-99m [99mTc]-labelled anti-PD-L1 single-domain antibody (NM-01) SPECT/CT, have the potential to improve the predictive value of PD-L1 assessment. This study aims to determine the inter- and intra-rater agreement of the quantitative measurement of [99mTc]NM-01 SPECT/CT in NSCLC. Methods Participants (n = 14) with untreated advanced NSCLC underwent [99mTc]NM-01 SPECT/CT at baseline (n = 3) or at baseline plus 9-week follow-up (n = 11). [99mTc]NM-01 uptake (of primary lung, lymph node, thoracic and distant metastases, and healthy reference tissues) was measured using SUVmax and malignant lesion-to-blood pool ratios with Siemens xSPECT Broad Quantification software by three independent raters. Intraclass correlation coefficients (ICC) were calculated and Bland–Altman plot analysis performed to determine inter- and intra-rater agreement. Results There was excellent inter-rater agreement of manual freehand SUVmax scores of primary lung tumour (T; n = 25; ICC 1.00; 95% CI 0.99–1.00), individual lymph node metastases (LN; n = 56; ICC 0.97; 95% CI 0.95–0.98), thoracic metastases (ThMet; n = 9; ICC 0.94; 95% CI 0.83–0.99) and distant metastases (DisMet; n = 21; ICC 0.91; 95% CI 0.83–0.96). The inter-rater ICCs of tumour-to-blood pool (T:BP), LN:BP, ThMet:BP and DisMet:BP measures of [99mTc]NM-01 uptake also demonstrated good or excellent agreement. Manual freehand scoring of T, LN, ThMet, DisMet and their ratios using [99mTc]NM-01 SPECT/CT following a 28-day interval was consistent for all raters with good or excellent intra-rater agreement demonstrated (ICCs range 0.86–1.00). Conclusion Quantitative assessment of [99mTc]NM-01 SPECT/CT in NSCLC, using SUVmax of malignant primary or metastatic lesions and their ratios with healthy reference tissues, demonstrated good or excellent inter- and intra-rater agreement in this study. Further validation with ongoing and future larger cohort studies is now warranted. Clinical trial registration ClinicalTrials.gov identifier no. NCT04436406 (registered 18th June 2020; available at https://clinicaltrials.gov/ct2/show/NCT04436406 ) and NCT04992715 (registered 5th August 2021; available at https://clinicaltrials.gov/ct2/show/NCT04992715 ).